1, 3‐ß‐D‐glucan concentrations in blood products predict false positive post‐transfusion results. Issue 1 (18th November 2015) - Liss, B.; Cornely, O. A.; Hoffmann, D.; Dimitriou, V.; Wisplinghoff, H.
Summary: 1, 3‐ß‐D‐glucan (BDG) is increasingly used to diagnose invasive fungal infections (IFI), although false positive results are a concern. To evaluate the potential interaction of blood products with the BDG assay, human albumin (HA), fresh frozen plasma (FFP), undiluted platelet transfusion (UPT) and packed red blood cells (PRBC) were tested for their BDG content using two different b‐D‐glucan tests. UPTs tested negative, FFP, PBRC and HA tested positive for BDG. In serial dilution, BDG concentration correlated with blood product concentration. To investigate the clinical impact of blood product transfusions, we measured BDG levels before and after the transfusion in three patients (2 PRBC, 1 HA). In the patients receiving PRBC transfusions, BDG values increased from 13 and 17 pg ml −1 to 183 and 361 pg ml −1, the HA transfusion increased the serum level from 42 to 58 pg ml −1 . BDG concentrations measured in blood products can be used to predict false positive BDG results.